Modern payment systems and their importance for financial stability ("Journal "U". Economy. Management. Finance.", 2026)
The article examines the significance of modern payment systems for financial stability. It investigates the impact of payment infrastructure, cashless settlements, and digital technologies on the resilience of monetary circulation. Special attention is given to the role of the national payment system in reducing risks and ensuring uninterrupted settlements. The study demonstrates that developing payment infrastructure serves as a key factor in enhancing the efficiency of the financial system and maintaining the stability of economic ties.
Keywords: payment systems; financial stability; cashless payments; payment infrastructure; national payment system; digitalization; money circulation